Exchange Rate Fluctuations, Oil Prices and Economic Performance: Empirical Evidence From Nigeria - OSIGWE, Augustine C. (International Journal of Energy Economics and Policy, 2015)
The dominance of oil in the Nigeria’s external sector and as its major source of revenue is not in dispute. This therefore necessitates the need to probe the nexus and the magnitude of the effects of fluctuation in the exchange rate on oil price and on how it impacts the Nigeria’s economic performance. Against this background, this study evaluated the effects of exchange rate fluctuations on crude oil price as well as on economic performance, simultaneously. The Ordinary Least Square (OLS) and the Two Stage Least Squares (TSLS) estimation techniques were employed. The study found that real exchange rate has a positive effect (1.2 per cent) on the Nigeria’s economic performance. We also found that a one percentage increase in the price of oil would positively influence the economic performance of Nigeria by the magnitude of 4 per cent. The R2 shows that 82 per cent deviation in the gross domestic product was captured by the explanatory variables whereas the J-statistics of the model is insignificant, thus, confirming the relevance and validity of the instruments used. Keywords: Exchange Rate; Oil Prices; Economic Performance JEL Classification: E3; F41; F43